Efficient succinic acid production from lignocellulosic biomass by simultaneous utilization of glucose and xylose in engineered Escherichia coli - Liu, Rongming; Liang, Liya; Li, Feng; Wu, Mingke; Chen, Kequan; Ma, Jiangfeng; Jiang, Min; Wei, Ping; Ouyang, Pingkai (Bioresource technology, 2013)
•We constructed a recombinant Escherichia coli strain named BA305.•BA305 improved utilization of glucose and xylose anaerobically.•BA305 consumed sugar mixture simultaneously during anaerobic fermentations.•Fed-batch fermentation of sugarcane bagasse hydrolysate was achieved in BA305.•39.3 g L−1 succinic acid was generated by BA305 in the hydrolysate fermentation. To enhance succinic acid formation during xylose fermentation in Escherichia coli, overexpression of ATP-forming phosphoenolpyruvate carboxykinase (PEPCK) from Bacillus subtilis 168 in an ldhA, pflB, and ppc deletion strain resulted in a significant increase in cell mass and succinic acid production. However, BA204 displays a low yield of glucose fermentation and sequential glucose–xylose utilization under regulation by the phosphotransferase system (PTS). To improve the capability of glucose fermentation and simultaneously consume sugar mixture for succinic acid production, a pflB, ldhA, ppc, and ptsG deletion strain overexpressing ATP-forming PEPCK, named E. coli BA305, was constructed. As a result, after 120h fed-batch fermentation of sugarcane bagasse hydrolysate, the dry cell weight and succinic acid concentration in BA305 were 4.58gL−1 and 39.3gL−1, respectively.